PENINGKATAN PEMBERDAYAAN PEREMPUAN DALAM KEWIRAUSAHAAN - Nurjaya, Nurjaya; Basar, Nur Fatwa; Asmawiyah, Asmawiyah (Arunika: Jurnal Pengabdian Masyarakat, 2023)
The involvement of women in empowerment activities is closely related to the ability to improve the economic condition of the family. Innovative activities allow them to learn various skills to earn income and expand their network, because they are connected to opportunities and innovation. This service activity was carried out in the Tumappua Village, Pangkajene District, Pangkep Regency. The method used is a women's empowerment workshop in entrepreneurship. The result of this community service activity is the increased ability and skills of women in entrepreneurship